2004
DOI: 10.1093/carcin/bgh092
|View full text |Cite
|
Sign up to set email alerts
|

Recombination at chromosomal sequences involved in leukaemogenic rearrangements is differentially regulated by p53

Abstract: Chromosomal translocations and retroviral integration events at breakpoint cluster regions (bcrs) have been associated with leukaemias. To directly compare the effect of different cis-regulatory sequences on recombination, we adapted our SV40 based model system to the analysis of correspondingly selected bcrs from the TAL1, LMO2, retinoic acid receptor alpha (RARalpha) and MLL genes. We show that a 399 bp fragment from the MLL bcr is sufficient to cause a 3-4-fold stimulation of spontaneously occurring DNA exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 50 publications
5
41
0
Order By: Relevance
“…In support of this, the MLL bcr fragment may act in cis to promote spontaneous recombination 3-to 4-fold between simian virus 40 molecules that can be elevated by etoposide treatment. 71 Homology-mediated DSB repair in mammalian cells requires members of the RAD52 epistasis group. 72 Rad51 is central to most homologous recombination events; Rad51 forms nucleoprotein filaments on ssDNA, and mediates homologous pairing and strand exchange between DNA duplexes, 73,74 although single-strand annealing can be promoted by Rad52 in the absence of Rad51.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, the MLL bcr fragment may act in cis to promote spontaneous recombination 3-to 4-fold between simian virus 40 molecules that can be elevated by etoposide treatment. 71 Homology-mediated DSB repair in mammalian cells requires members of the RAD52 epistasis group. 72 Rad51 is central to most homologous recombination events; Rad51 forms nucleoprotein filaments on ssDNA, and mediates homologous pairing and strand exchange between DNA duplexes, 73,74 although single-strand annealing can be promoted by Rad52 in the absence of Rad51.…”
Section: Discussionmentioning
confidence: 99%
“…In the first work, 157 it was discovered that p53 upregulates recombination at a fragment of the RARa breakpoint cluster region, which comprises two perfect topoisomerase 1 recognition sequences. Treatment with the topoisomerase 1 inhibitor camptothecin indicated an epistatic relationship between p53 and topoisomerase 1 with respect to recombination enhancement.…”
Section: P53 Participates In Novel Recombination Stimulatory Pathwaysmentioning
confidence: 99%
“…95 The newly discovered recombination stimulatory activity of p53 that may be connected to topoisomerase 1-dependent excision repair is a good candidate for this gain-of-function phenotype. 157 Thus, failure to suppress aberrant HR coupled to the remaining capacity to stimulate DNA exchange via this topoisomerase 1 repair pathway would be expected to generate a gain-of-function phenotype in recombination, which also could explain the rise in gene amplification observed with some mutant p53 proteins. Specific recruitment and differential modification of the p53 molecule might coordinate the different repair-related activities, as suggested by the tightly regulated interactions of wild-type p53 with topoisomerase 1 in response to DNA damage.…”
mentioning
confidence: 99%
“…DNA junction binding in particular has been connected to a possible role of wtp53 in the inhibition of gene conversion events (Dudenho¨ffer et al, 1998;Akyu¨z et al, 2002), and, more recently, of replication-associated recombination processes Saintigny and Lopez, 2002). In further support for an antirecombinogenic role of p53 in a DNA sequence-independent manner, p53 was shown to inhibit strand exchange promoted by Rad51 on randomly chosen DNA substrates (Yoon et al, 2004) and to downregulate recombination with different sequences (Boehden et al, 2004). Finally, on the basis of recombination measurements with p53 mutants, it was demonstrated that transcriptional transactivation, which relies on sequence-specific DNA recognition, and consensus sequence-independent downregulation of recombination are genetically separable functions of p53 (Dudenho¨ffer et al, 1999;Saintigny et al, 1999;Willers et al, 2000;Akyu¨z et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Finally, on the basis of recombination measurements with p53 mutants, it was demonstrated that transcriptional transactivation, which relies on sequence-specific DNA recognition, and consensus sequence-independent downregulation of recombination are genetically separable functions of p53 (Dudenho¨ffer et al, 1999;Saintigny et al, 1999;Willers et al, 2000;Akyu¨z et al, 2002). However, recently published data challenged the notion that p53 regulates homologous recombination in a negative and sequence-independent manner exclusively (Boehden et al, 2004). Thus, when analysing the role of p53 in recombination involving leukemia-related sequences, wtp53 displayed a stimulatory activity directed toward a fragment from the RARa breakpoint cluster region (bcr).…”
Section: Introductionmentioning
confidence: 99%